Aspirasi Pendidikan Siswa Kecamatan Cisauk: Studi Kasus di SDN Mekarwangi - Helsa Surya; Rani Rishanty; Leonarda Anggia; Juanita Putrianawati; Hadyan Dhiozandi; Ignatius Darma Juwono (Universitas Katolik Indonesia Atma Jaya, 2017)
Although the Indonesia's constitution guarantees that every child has access to basic education, which was strengthened by the National Education System Acts (Legislation number 20 in 2003), there are still plenty of Indonesian children who do not have the luxury to enjoy education. Whether it was due to remote location with lacking facilities, poverty, or cultural factor, plenty of obstacle for children to enroll in 9 years basic education. This creates a cyclical pattern of poverty within the society. This paper intends to describe educational aspiration of primary school children in a village within the District of Cisauk, Banten Province, Indonesia. 81 students of grade 4 to 6 and 8 teachers in the school were selected as participants of the study. Data from interviews and FGD reveal that despite the relatively close distance to Jakarta as the capital of Indonesia, the village still lacks of education facilities for children to enroll and the social economic of the village provide a big stumbling block for children to enroll in education. Hence the students’ aspiration to get into secondary school is relatively low. The paper will also describe a social intervention program conducted by students of Master in Professional Psychology Program, aimed at the children, to broaden the children’ horizon that provide impetus for them to continue their education to the next level, as high as can be.